2001
DOI: 10.1046/j.1523-1755.2001.060003982.x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of parathyroid hormone-related protein in folic acid-induced acute renal failure

Abstract: Renal PTHrP was rapidly and transiently increased in rats with folic acid-induced acute renal failure, featuring as an early response gene. In addition, changes in ACE and Ang II expression were also found in these animals. PTHrP induces a mitogenic response in folic acid-damaged renal tubular cells both in vivo and in vitro. Our results support the notion that PTHrP up-regulation participates in the regenerative process in this model of acute renal failure and is a common event associated with the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 36 publications
7
63
2
Order By: Relevance
“…Many genes have been reported to be upregulated after tubular injury. Egr-1 (28), c-fos (28), c-myc (29), and the genes encoding heat shock protein-70 (30) and parathyroid hormonerelated protein (PTHrP) (31) have been shown to be upregulated in the very early phase after injury. Their upregulation was detected as early as within a few hours and returned to baseline within 1 d. These are considered the early response genes to renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes have been reported to be upregulated after tubular injury. Egr-1 (28), c-fos (28), c-myc (29), and the genes encoding heat shock protein-70 (30) and parathyroid hormonerelated protein (PTHrP) (31) have been shown to be upregulated in the very early phase after injury. Their upregulation was detected as early as within a few hours and returned to baseline within 1 d. These are considered the early response genes to renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…From then on, the majority of investigations have studied experimental nephropathies characterized by tubular affectation (Fiaschi-Taesch et al, 2004;Largo et al, 1999;Lorenzo et al, 2002;Ortega et al, 2005;Santos et al, 2001). Ischemic and toxic injury to renal tubular epithelial cells can cause both acute and chronic renal failure depending on the intensity of and exposure time to the damage (Humes et al, 1995;Lieberthal & Levine, 1996).…”
Section: Pthrp In Acute Renal Injurymentioning
confidence: 99%
“…Several growth factors and cytokines, acting in an autocrine and paracrine manner, appear to participate in the repair process of the tubular epithelium in this setting (Fiaschi-Taesch et al, 2004;Gobe et al, 2000;Humes et al, 1995;Matsumoto & Nakamura, 2001;Vukicevic et al, 1998). The mitogenic features of PTHrP and its early overexpression after renal injury in experimental models of acute renal failure (ARF), induced by either ischemia or nephrotoxins, initially suggested that PTHrP could participate in the regenerative process after ARI (Santos et al, 2001;Soifer et al, 1993). However, this putative role of PTHrP in the acutely damaged kidney was intriguing, since the PTH1R gene was found to be rapidly downregulated following ARI (Santos et al, 2001;Soifer et al, 1993).…”
Section: Pthrp In Acute Renal Injurymentioning
confidence: 99%
See 2 more Smart Citations